Perancangan Interior Sekolah Bahasa Mandarin Di Surabaya - Stefanie Felicia Ekaseputra (Intra, 2015)
Mandarin has become one of the most popular and internationally known language after English. Due to the globalization need and the increasing value of Mandarin as the second international language, comes the need of a Mandarin learning center. By designing a public facility that develop courses into a specialized Mandarin language school, it is hoped that the learning of Mandarin can be more effective than just by a course. The design area includes lobby, administration room, cafe, class rooms, extracurricular rooms, teacher room, library, headmaster room, computer laboratory and meeting point area. Since the school close relation to the culture of China, the applied design concept is based on the Chinese design characters and modernity by adopting the concept of calligraphy elements.